Trouble makers : dissent over foreign policy 1792 - 1939 - Taylor, A. J. P. (London, 1964)
This is not unique to Great Britain. Given a world of sovereign Powers, men will often disagree which partners to choose and which es. Mr. Kennan and Professor Mor genthau may complain that the foreign policy of a democracy is weak and confused, and may sigh for the resolute authori tarianism of the ancien régime. The advisers of absolute monarchs disputed just as much, and often with more disas trous results. Think for instance of the way in which Austria lost her supremacy in Germany simply because her statesmen could not make up their minds whether to go resolutely with Prussia or resolutely against her. Take the confusion of coun sels which brought Russia to humiliation at the Congress of Berlin or, a generation later, to defeat in the Russo-Japanese war. We are apt to say that a foreign policy is successful only when the country, or at any rate the governing class, is united behind it. In reality, every line of policy is repudiated by a section, often by an influential section, of the country con cerned. A foreign minister who waited until everyone agreed with him would have no foreign policy at all.
Keywords: International relations-1939 2. Great Britain